Karakteristik Fenotip dan Genotip Gen GH (Growth Hormon) pada Ayam Tolaki - Muhammad Amrullah Pagala; Achmad Selamet Aku; Rusli Badaruddin; Hamdan Has (Universitas Halu Oleo, 2018)
This study aims to improve the genetic quality of local chickens through genetic approaches and phenotypic characterization for selection purposes. The cGH gene (Chicken Growth Hormone) is one of the genes responsible for local chicken growth traits. Tolaki chicken is a local chicken from Southeast Sulawesi. This study uses the phenotyping method of production and genotyping traits with PCR technique. A total of 50 parents of tolaki chicken were kept 4 weeks. The results showed average body weight of tolaki chicken ranged from 1,395 kg - 1,910 kg, average body weight gain was 58,78 (g / head / week), feed consumption was 81,37 (g / head / day) and ration conversion 9,68. Body weight gain in males was slightly higher (60.30 g / head / mg) compared to females (58.42 g / head / mg). In this study, the presence of the tolaki chicken cGH gene was identified through DNA extraction and amplification through a PCR machine with a length of DNA section of 399 bp.